Association of body burden of mercury with liver function test status in the U.S. population - Lin, Yu-Sheng; Ginsberg, Gary; Caffrey, James L.; Xue, Jianping; Vulimiri, Suryanarayana V.; Nath, Raghu G.; Sonawane, Babasaheb (Environment international, 2014)
The majority of mercury (Hg) exposure in the US population is from consumption of fish contaminated with methylmercury (MeHg). Since inorganic Hg is the predominant form excreted in the feces and urine, hepatic biotransformation is a critical step in its normal clearance. This study was set to test the hypothesis that compromised liver function is associated with body burden of Hg as indirectly reflected by Hg sampled in blood and urine. From the National Health and Nutrition Examination Survey (NHANES, 2003–2008), 3769 adults aged 20years and above were selected for analysis. Hepatic function was inferred from the three standard serum liver-related enzyme activities, aspartate aminotransferase (AST), alanine aminotransferase (ALT), and γ-glutamyltransferase (GGT). Multivariate regression models were used to examine the associations of interest. Although urinary Hg was significantly correlated with serum Hg, the blood–urinary Hg relationship was influenced by liver function, which is also a function of demographic and lifestyle factors (e.g., gender). Although the results were only marginally significant for examined enzymes (p=0.06–0.08), urinary Hg tended to be lower among subjects with elevated liver enzymes, as compared to those with normal enzyme measurements. Conversely, MeHg generally represents a higher fraction of the total circulating Hg among those with elevated liver enzyme levels, especially among participants with elevations in all three enzymes (p=0.01). In conclusion, this population-based study identified an association between liver function, serum Hg and urinary Hg. Urinalysis may not be the optimal approach to monitor Hg elimination toxicokinetics or Hg exposure, since the majority of Hg excretion is fecal and the fidelity of urinary excretion may depend on healthy liver function. Future prospective studies are warranted to expand these findings. •Hg content in blood and urine are correlated with each other.•The blood-urinary Hg relationship suggests that urinary excretion plays a role in Hg elimination.•The association of interest is influenced by liver function which is also affected by host factors.•One may need to consider demographic and lifestyle determinants while evaluating Hg toxicokinetics.